BAGI HASIL USAHA KAPAL TAMBANG EMAS DI NAGARI KOTO TUO KABUPATEN SIJUNJUNG PRESPEKTIF FIQH MUAMALAH - Ulfi Febrianti; Irma Suryani (Institut Agama Islam Negeri Batusangkar, 2021)
This paper aims to explain the fiqh muamalah review of the contract agreement and the pattern of the profit sharing agreement system for gold mining vessels in Nagari Koto Tuo, Sijunjung Regency. This research is a qualitative research. Data collection techniques through interviews and observation. Primary data sources consist of land owners, ship owners and workers, as well as supporting data consisting of library data related to profit sharing. The data analysis technique used is descriptive qualitative analysis. This study found that the contract made in the gold mining ship business is a cooperation agreement. The contract takes place orally and in writing. First, the form of the contract in the gold mining ship business, the land owner and the ship owner are called syirkah and the ship owner with other investors is called syirkah mufawadah. Second, the form or method of managing the gold mining ship business, ship owners and workers, is called syirkah. Third, profit sharing in the gold mining ship business of land owners, ship owners, and workers is called syirkah mudharabah. However, their profit sharing system is a new profit sharing system, namely a profit sharing system based on their knowledge alone. Therefore, there is an element of ambiguity or gharar in the profit-sharing system that they do. However, this can still be done as long as there is an agreement.